Isolated Eight and Half Syndrome, a Rare Neuro-ophthalmic Presentation: A Case Report - Tamrakar Karki, Karuna (Eastern Green Neurosurgery, 2022)
Eight and half syndrome is one of the rare neurological disorders, which is usually overlooked in our clinical practice. Here I report 58 years-old hypertensive Indian gentleman presented with horizontal gaze palsy and facial weakness.